TWO POSITIONS ON THE NAGORNO-KARABAKH WAR: RUSSIAN AND TURKISH (1990-1994) - SOULEIMANOV, Emil; EVOYAN, Lia (CENTRAL ASIA AND THE CAUCASUS, 2012)
The winter months of 2011/2012 marked the 20th anniversary of the beginning of full-scale warfare in the highlands of Nagorno-Karabakh, de jure an Azerbaijani enclave inhabited mostly by ethnic Armenians and controlled by the latter and an unrecognized republic that has essentially been claiming independence since the final days of the Soviet Union. The armed conflict in Nagorno-Karabakh and adjacent are-as, which with various levels of intensity lasted from the end of the 1980s until 1994 when a ceasefire brokered by Moscow was signed, has greatly shaped the post-Soviet independence of Armenia and Azerbaijan, contributing to the long-term fragmentation of the Southern Caucasus and complicating its integration into world affairs. Indeed, the fundamentals of the regional power constellation that has endured since then were laid down at the beginning of the 1990s, with the Karabakh conflict playing a significant role in it. As of yet, years after the end of the Karabakh war, a definite solution to the conflict still seems to be out of sight, with both the Azerbaijani and the Armenian governments occasionally making use of militarist rhetoric in order to either reverse the current status quo in their favor or ensure it, respectively.1 Small-scale fighting in the borderline areas of the disputed territory has never completely stopped, and every year hundreds of Armenian and Azerbaijani soldiers fall victim to occasional positional warfare. Importantly, the foreign political agendas of Baku and Erevan have been heavily centered on the Karabakh issue, with Azerbaijan routinely investing billions of dollars of its oil and natural gas revenues in the improvement of its military capabilities and advocating on the international scene for regaining the territories lost in the conflict.2 Like other post-Soviet states, Armenia has also recently been experiencing what a number of commentators both inside and outside this South Caucasian country regard as a certain reduction in the nation’s economic independence in favor of Russia. Vis-à-vis Baku’s prospective attempts to restore its territorial integrity by launching a renewed war effort in Nagorno-Karabakh, the Armenians consider the rather significant concessions the Armenian Republic has made to its major ally north of the Greater Caucasus Mountain Range with respect to its economic and political autonomy to be instrumental in containing the Azerbaijani (and Turkish) threat. As a “lesser evil,” they are still being accepted by mainstream Armenian public opinion, even though opposition opinions are articulated from time to time by local intellectuals. Interestingly, many Armenian politicians tend to point at Moscow’s stance in the 2008 Russo-Georgian war over South Ossetia; according to the prevailing view, it indicated the Kremlin’s commitment to defend its remaining bastions in the Southern Caucasus providing full-scale support of its allies.